The Effect of Treatment for Epilepsy Associated with Malignant Neoplasms of the Brain: a Literature Review - Y. Wang; L. F. Mufazalova; N. A. Mufazalova; V. I. Korunas; N. V. Ilyasova; A. V. Vasilchenko; A. V. Samorodov (Креативная хирургия и онкология, 2023)
Introduction. Epilepsy is a frequent complication in patients with malignant neoplasms of the brain. However, despite an extensive number of studies, anticonvulsants with antitumor activity have not been studied enough. The purpose of this study was to evaluate the efficacy and tolerability of brivaracetam and levetiracetam as an additional therapy in patients with malignant brain tumors, as an anticonvulsant and antitumor agent. Materials and methods. The search was carried out in the electronic databases PubMed/MEDLINE, EMBASE, Cochrane Library until June 2023. Screening and selection of studies was carried out according to the recommendations of PRISMA. The search included a combination of queries related to “glioma”, “epilepsy”, “antiepileptic drugs” and “efficacy”. From all the relevant articles, three different results were extracted for both mono- and polytherapy: adult patients with brain malignancies; ≥55 % of patients with proven or suspected glioma using histological examination; ≥10 patients receiving the same AED. Results. The data regarding levetiracetam are contradictory. In terms of research, this drug has shown not only anticonvulsant activity, but also antitumor activity. Other researchers point to the absence of antitumor activity in levetiracitam. Brivaracetam is an effective anticonvulsant drug that has shown antitumor activity in studies, but there are not enough studies to make an adequate conclusion. Discussion. The results obtained on the antitumor activity of levetiracetam are quite contradictory. Perhaps this is due to the heterogeneity of patient populations in terms of morphological examination of the tumor, different patients receiving concomitant treatment, and the prevalence of the tumor process. With regard to brivaracetam, it is not possible to give an adequate conclusion about an effective combination of antitumor and anticonvulsant activity due to the insufficient number of studies to date. Conclusion. Levetiracetam and brivaracetam have shown high efficacy in the symptomatic treatment of epilepsy associated with brain tumors. However, data on the presence of antitumor activity in these drugs is contradictory and requires further research.